Health Sensors, Smart Home Devices, and the Internet of Medical Things: An Opportunity for Dramatic Improvement in Care for the Lower Extremity Complications of Diabetes - Basatneh, Rami; Najafi, Bijan; Armstrong, David G (Journal of diabetes science and technology, 2018)
The prevalent and long-neglected diabetic foot ulcer (DFU) and its related complications rank among the most debilitating and costly sequelae of diabetes. With the rise of the Internet of medical things (IoMT), along with smart devices, the med-tech industry is on the cusp of a home-care revolution, which could also create opportunity for developing effective solutions with significant potential to reduce DFU-associated costs and saving limbs. This article discusses potential applications of IoMT to the DFU patient population and beyond. To better understand potential opportunities and challenges associated with implementing IoMT for management of DFU, the authors reviewed recent relevant literatures and included their own expert opinions from a multidisciplinary point of view including podiatry, engineering, and data security. The IoMT has opened digital transformation of home-based diabetic foot care, as it enables promoting patient engagement, personalized care and smart management of chronic and noncommunicable diseases through individual data-driven treatment regimens, telecommunication, data mining, and comprehensive feedback tailored to individual requirements. In particular, with recent advances in voice-activated commands technology and its integration as a part of IoMT, new opportunities have emerged to improve the patient's central role and responsibility in enabling an optimized health care ecosystem. The IoMT has opened new opportunities in health care from remote monitoring to smart sensors and medical device integration. While it is at its early stage of development, ultimately we envisage a connected home that, using voice-controlled technology and Bluetooth-radio-connected add-ons, may augment much of what home health does today.